2010
DOI: 10.1007/s12155-010-9089-z
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Enhancing the Effectiveness of Metagenomic-based Enzyme Discovery in Lignocellulolytic Microbial Communities

Abstract: Producing cellulosic biofuels from plant material has recently emerged as a key US Department of Energy goal. For this technology to be commercially viable on a large scale, it is critical to make production cost efficient by streamlining both the deconstruction of lignocellulosic biomass and fuel production. Many natural ecosystems efficiently degrade lignocellulosic biomass and harbor enzymes that, when identified, could be used to increase the efficiency of commercial biomass deconstruction. However, ecosys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 99 publications
(91 citation statements)
references
References 55 publications
5
83
0
3
Order By: Relevance
“…Adaptive cultivation on other feedstocks, such as lignin, cellulose, and CMC, has also generated simplified communities and, along with this study, indicates that this method is a useful tool for developing simplified biomass-degrading consortia tailored to deconstruct a designated feedstock under defined conditions, such as temperature or pH (6,22,26).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Adaptive cultivation on other feedstocks, such as lignin, cellulose, and CMC, has also generated simplified communities and, along with this study, indicates that this method is a useful tool for developing simplified biomass-degrading consortia tailored to deconstruct a designated feedstock under defined conditions, such as temperature or pH (6,22,26).…”
Section: Discussionmentioning
confidence: 69%
“…DNA was isolated from the pellets generated during isolation of culture supernatants described above. DNA isolation and sequencing were performed as previously described (6). Sequencing tags were quality trimmed and analyzed using the pyroclust version of the software tool PyroTagger (http://pyrotagger.jgi-psf.org) with a 220-bp sequence length threshold and an accuracy of 10% for low-quality bases (9,19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, engineered culture conditions are used to enrich for desirable traits and lead to the discovery of functional microbial consortia or specific microorganisms. For example, starting with microbial communities collected from compost and soil environments, a selection of simplified communities have been found that can deconstruct lignocellulosic biomass in extreme conditions, such as high temperature, high-solid loading, and low moisture (DeAngelis et al 2010;Jimenez et al 2014;Reddy et al 2013;Simmons et al 2014;Yu et al 2015). The enrichment process generates less complex lignocellulolytic microbial communities that can facilitate targeted discovery of potential enzymes and microorganisms for biomass deconstruction .…”
Section: Discovering and Screening For Il Tolerant Microorganisms Relmentioning
confidence: 99%
“…Attempts to address the various limitations of functional metagenomics include selective enrichment of the uncultured microbial communities prior to construction of metagenomic [59,109,[127][128][129][130][131] to improve functional expression of heterologous genes. Recently, metagenomic libraries from thermophilic habitats were successfully screened for novel esterases using the bacterium Thermus thermophilus as host [132].…”
Section: Mining Metagenomes For Novel Acxesmentioning
confidence: 99%